Whole-Genome Shotgun Sequencing for Nasopharyngeal Microbiome in Pre-school Children With Recurrent Wheezing - Song, Yuping; Hou, Jinpao; Kwok, Jamie Sui Lam; Weng, Haoyi; Tang, Man Fung; Wang, Maggie Haitian; Leung, Agnes Sze Yin; Tao, Kin Pong; Wong, Gary Wing Kin; Chan, Renee Wan Yi; Tsui, Stephen Kwok Wing; Leung, Ting Fan (Frontiers in Microbiology, 2022)
Microbiome mediates early-life immune deviation in asthma development. Recurrent wheeze (RW) in pre-school years is a risk factor for asthma diagnosis in school-age children. Dysbiosis exists in asthmatic airways, while its origin in pre-school years and relationship to RW was not clearly defined. This study investigated metagenomics of nasopharyngeal microbiome in pre-school children with RW. We applied whole-genome shotgun sequencing and human rhinovirus (HRV) detection on nasopharyngeal samples collected from three groups of pre-school children: (i) RW group: 16 children at-risk for asthma who were hospitalized for RW, (ii) inpatient control (IC): 18 subjects admitted for upper respiratory infection, (iii) community control (CC): 36 children without respiratory syndromes. Sequence reads were analyzed by MetaPhlAn2 and HUMAnN2 algorithm for taxonomic and functional identification. Linear discriminant analysis effect size (LEfSe) analysis was used to identify discriminative features. We identified that Moraxella catarrhalis and Dolosigranulum pigrum were predominant species in nasopharynx. RW had lower alpha diversity (Shannon diversity index) than CC (0.48 vs 1.07; P=.02), characterized by predominant Proteobacteria. LEfSe analysis revealed D. pigrum was the only discriminative species across groups (LDA=5.57, P=.002), with its relative abundance in RW, IC and CC being 9.6%, 14.2% and 37.3%, respectively (P<.05). LEfSe identified five (ribo)nucleotides biosynthesis pathways to be group discriminating. Adjusting for HRV status, pre-school children with RW have lower nasopharyngeal biodiversity, which is associated with Proteobacteria predominance and lower abundance of D. pigrum. Along with discriminative pathways found in RW and CC, these microbial biomarkers help to understand RW pathogenesis.